2016
DOI: 10.7567/jjap.55.02bc20
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and scintillation properties of La- and La,Ag-doped CsPbCl3 single crystals

Abstract: We analyzed the luminescence and scintillation properties of CsPbCl3 single crystals. La and Ag were chosen as the dopants, although Ag proved to have little effect on the scintillation properties. In the photoluminescence spectra, in addition to the free exciton band at 425 nm, an additional band was observed at 440 nm at low temperatures for the La-doped crystals. The scintillation spectrum of the undoped crystal was composed of the free exciton band and a broad band at 600 nm, which is ascribed to lattice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…It should be pointed out that Yb 3+ contamination can be excluded for this emission band due to the absence of such peak after Lu 3+ doping (see Figure S4). Interestingly, increasing the Er 3+ concentration leads to a progressive suppression of this emission band (see Figure S2), which may be related to intrinsic deep traps in CsPbCl 3 NCs, such as Cl vacancies or undercoordinated Pb atoms. , A similar NIR emission at 930 nm assigned to the defective states of oxygen vacancies in Fe-doped SrSnO 3 perovskite was also noticed by Muralidharan et al Cl vacancies are commonly observed in perovskite materials and seen as a predominant source of electron trapping. , However, such vacancies can be removed by B-site doping with divalent metal ions or trivalent lanthanide ions, which favor the introduction of negatively charged Cl – ions for charge compensation . To verify that the quenching of the 994 nm emission band by Er 3+ incorporation can be ascribed to the removal of defects rather than to the activation of additional energy-transfer pathways, we extended our analysis to Lu 3+ -doped CsPbCl 3 NCs as reference.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…It should be pointed out that Yb 3+ contamination can be excluded for this emission band due to the absence of such peak after Lu 3+ doping (see Figure S4). Interestingly, increasing the Er 3+ concentration leads to a progressive suppression of this emission band (see Figure S2), which may be related to intrinsic deep traps in CsPbCl 3 NCs, such as Cl vacancies or undercoordinated Pb atoms. , A similar NIR emission at 930 nm assigned to the defective states of oxygen vacancies in Fe-doped SrSnO 3 perovskite was also noticed by Muralidharan et al Cl vacancies are commonly observed in perovskite materials and seen as a predominant source of electron trapping. , However, such vacancies can be removed by B-site doping with divalent metal ions or trivalent lanthanide ions, which favor the introduction of negatively charged Cl – ions for charge compensation . To verify that the quenching of the 994 nm emission band by Er 3+ incorporation can be ascribed to the removal of defects rather than to the activation of additional energy-transfer pathways, we extended our analysis to Lu 3+ -doped CsPbCl 3 NCs as reference.…”
Section: Resultssupporting
confidence: 63%
“…Although we detected Er 3+ ions in purified CsPbCl 3 NCs, Er 3+ -doped NCs exhibit only a faint Er 3+ emission at ∼1.54 μm in concentrated samples (see Figure S2), which suggests a weak Er 3+ sensitization. For both undoped and Er 3+ -doped CsPbCl 3 NCs, we observed a NIR emission feature centered at 994 nm with a full width at half-maximum (fwhm) of ∼55 nm, whereas a defect-related visible emission around 600 nm was observed by Watanabe et al This 994 nm emission has a broad excitation profile that closely resembles the excitation profile of the CsPbCl 3 band-edge emission (see Figure S3). The above result indicates that the 994 nm emission band originates from a state directly fed by the band-edge electron–hole pairs.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…No other emission is observed from the La 3+ :CsPbCl 3 NCs. A similar trap PL band has been reported for La 3+ :CsPbCl 3 single crystals, suggesting that this is an internal lattice defect not associated with the NC surfaces. This trap luminescence in these La 3+ :CsPbCl 3 NCs is very bright below ∼80 K, but increasing the temperature above ∼80 K causes excitonic PL to grow in at the expense of the broad trap PL, and the overall PL decreases substantially (see the Supporting Information for additional data).…”
supporting
confidence: 81%
“…Moreover, the TLYC crystal can distinguish gamma-ray and neutron radiations by pulse shape discrimination (PSD). (9) Presently, our group has also reported some new halide scintillator materials with low hygroscopicity and large Z eff values, namely, CsPbCl 3 , (10) Cs 3 BiCl 6 , (11) Rb 2 HfCl 6 , (12) TlMgCl 3 , (13) TlCdCl 3 , (14) and Cs 2 HfBr 6 . (15) In particular, Rb…”
Section: Introductionmentioning
confidence: 98%